Oral Administration of Lactobacillus rhamnosus GG Ameliorates Salmonella Infantis-Induced Inflammation in a Pig Model via Activation of the IL-22BP/IL-22/STAT3 Pathway - Yang, Gui-Yan; Yu, Jiao; Su, Jin-Hui; Jiao, Lian-Guo; Liu, Xiao; Zhu, Yao-Hong (Frontiers in Cellular and Infection Microbiology, 2017)
The high rate of Salmonella enterica serovar Infantis (S. Infantis) infection poses significant risk for the development of non-typhoidal Salmonella gastroenteritis. However, efficient strategies to prevent or treat the infection remain elusive. Here, we explored the effect of the probiotic Lactobacillus rhamnosus GG (LGG) administration in preventing S. Infantis infection in a pig model. Probiotic LGG (1.0 × 1010 CFU/day) was orally administered to newly weaned piglets for 1 week before S. Infantis challenge. LGG pretreatment reduced the severity of diarrhea and alleviated intestinal inflammation caused by S. Infantis. Pre-administration of LGG excluded Salmonella from colonization of the jejunal mucosa but increased the abundance of Bifidobacterium in the feces. LGG promoted the expansion of CD4+ T-bet+ IFNγ+ T cells but attenuated S. Infantis–induced increases in the percentage of CD4+ IFNγ+ T cells and serum interleukin (IL)-22 levels in peripheral blood after S. Infantis challenge. In the small intestine, LGG pretreatment upregulated expression of the transcription factor T-bet but downregulated the S. Infantis–induced increase of CD4+ IFNγ+ T cells in Peyer’s patches and IL-7R expression in the jejunum. Notably, LGG–treated pigs had enhanced expression of IL-22 and activated STAT3 in the ileum in response to S. Infantis infection. Pretreatment of pigs with LGG also elevated intestinal IL-22–binding protein production in response to S. Infantis challenge. In contrast, LGG consumption reduced the S. Infantis–induced increase in the number of CCL20-expressing cells in the jejunum. Our results suggest that the mechanism by which LGG ameliorates the intestinal inflammation caused by S. Infantis involves the upregulation of T-bet, activation of STAT3, and downregulation of CCL20.